2003
DOI: 10.1093/humrep/deg215
|View full text |Cite
|
Sign up to set email alerts
|

Contraception: from accessibility to efficiency

Abstract: The importance of-and the reasons mentioned for-contraceptive failure show a misadaptation between women's contraceptive needs and the method they use. Improving the training of family planning providers remains a major goal to ensure that women use a contraceptive method that fits their social and sexual lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
21

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 21 publications
4
57
1
21
Order By: Relevance
“…Bajos et al found that 72% of pregnancies terminated by an abortion occur among women using contraception [medical contraception -hormonal or intrauterine device (IUD) -in 30% of the cases] [11]. In these situations emergency contraceptive pill (EC) could be used, which is effective and safe [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bajos et al found that 72% of pregnancies terminated by an abortion occur among women using contraception [medical contraception -hormonal or intrauterine device (IUD) -in 30% of the cases] [11]. In these situations emergency contraceptive pill (EC) could be used, which is effective and safe [12].…”
Section: Introductionmentioning
confidence: 99%
“…In these situations emergency contraceptive pill (EC) could be used, which is effective and safe [12]. Unfortunately, the frequency of EC use is low in unintended pregnancy risk cases and information campaigns should be targeted not only at women with irregular contraceptive practices but also at women who experience errors in the use of their regular contraceptive method [11,13]. Recent studies among women seeking an abortion estimated that 38% to 60% of pregnancies leading to abortions could have been avoided by using EC [14].…”
Section: Introductionmentioning
confidence: 99%
“…Informed choices in FP are associated with satisfaction and compliance with the method, and consequently with less failures [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados na área da sexualidade e do gênero apontam o quão difícil tem sido a gestão da sexualidade e da contracepção no par heterossexual, as difi culdades de uso regular de métodos anticoncepcionais, com ocorrência de gravidez imprevista e aborto em condições inseguras 2 para a saúde das mulheres (Bajos et al, 2002(Bajos et al, , 2003Cabral, 2012;Gonçalves et al, 2011;Luker, 1975;Spencer et al, 2014;Teixeira el al., 2012). As difi culdades de negociação entre os casais sobre o uso do preservativo masculino e/ou de outro método de proteção à gravidez, devido à forte hierarquia de gênero e uma cultura sexual que preconiza a "naturalidade" e a espontaneidade do ato sexual, impedem o planejamento prévio dos encontros sexuais, admitindo-se um certo grau de incerteza e do risco de se engravidar (Bozon;Heilborn, 2006;Cabral, 2011).…”
Section: Contexto Da Contracepção De Emergência No Brasilunclassified